2022
DOI: 10.1175/jcli-d-22-0234.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Locking of the MJO’s Southward Detour of the Maritime Continent: The Role of the Australian Monsoon

Abstract: This study investigates why the major convective envelope of the Madden-Julian Oscillation (MJO) detours to the south of the Maritime Continent (MC) only during boreal winter (December-March; DJFM). To examine processes affecting this MJO detour, the MJO-related variance of precipitation and column-integrated moisture anomalies in DJFM are compared with those in the seasons before (October-November; ON) and after (April-May; AM). While MJO precipitation variance is much higher in the southern MC (SMC) during D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…The importance of moisture transport and wind-evaporation feedback in the development of MJO convection over the SMC during the Australian monsoon season is consistent with the recent findings by Kang et al (2022). However, our result further reveals that the CES amplifies the MJO convection over the SMC, highlighting the importance of intraseasonal cross-equatorial winds in governing the magnitude of MJO detours during the active Australian monsoon season (see the illustration in Figure 5).…”
Section: Summary and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The importance of moisture transport and wind-evaporation feedback in the development of MJO convection over the SMC during the Australian monsoon season is consistent with the recent findings by Kang et al (2022). However, our result further reveals that the CES amplifies the MJO convection over the SMC, highlighting the importance of intraseasonal cross-equatorial winds in governing the magnitude of MJO detours during the active Australian monsoon season (see the illustration in Figure 5).…”
Section: Summary and Discussionsupporting
confidence: 92%
“…More recently, Kang et al. (2022) demonstrated that the MJO detour exhibits seasonality and is primarily observed during the Australian monsoon season (December to March, DJFM). This season provides a conducive background state for MJO development in the SMC, which is characterized by a stronger positive wind‐evaporation feedback due to the background westerly winds in the lower troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering several MJO events that passed eastward from the northern part of the MC region into the Pacific Ocean, follow-up studies are still needed. The impacts of interannual variabilities of the ENSO, the Australian monsoon, and solar insolation in the MC region on the eastward propagation of MJO events have been revealed in previous studies (Hagos et al, 2019(Hagos et al, , 2020Hu, Chen, et al, 2022;Kang et al, 2022;Kim et al, 2017), but the results above suggest that the occurrences of the MJO_SC and MJO_N events are not entirely determined by these interannual variability factors in the background. In addition, previous studies have demonstrated the possible effects of oceanic eddies (Hu et al, 2021;Wen et al, 2020), oceanic fronts (Bai et al, 2019;Chen et al, 2019Chen et al, , 2020; Guan…”
Section: Discussionmentioning
confidence: 68%
“…In the third and fourth sections, we will further investigate the differences in the accompanying climate effects and possible influencing mechanisms of oceanic processes. Furthermore, previous studies noted the impacts of interannual variability such as ENSO (Hagos et al, 2019;Hu, Wang, et al, 2022), Australian monsoon (Hagos et al, 2019;Kang et al, 2022;Kim et al, 2017), winter surface solar radiation in the MC region (Hagos et al, 2020) on the eastward propagation of MJO events during boreal winter. To remove the influence of interannual variability mentioned above, the anomalies are calculated by subtracting their annual winter average in the following sections.…”
Section: Methodsmentioning
confidence: 99%
“…One might immediately note that the “Maritime Continent (MC) barrier” (Zhang & Ling, 2017) likely plays a role in shaping the wavenumber‐2 MJO in DJF. During this season, the MJO frequently detours via the southern MC (Kang et al., 2022; Kim et al., 2017; Zhou et al., 2021; Zhou & Murtugudde, 2020) and might encounter a stronger MC barrier effect than during JJA (Li et al., 2020; Wang et al., 2022). Zhang and Dong (2004) also discussed that the two maximum centers of MJO convective signals over the Indian Ocean and western Pacific straddling zonally the MC, an area showing the minimum MJO variance (Sobel et al., 2008), might explain the wavenumber‐2 structure of the MJO in winter.…”
Section: Discussionmentioning
confidence: 99%